Discovery of Novel Antibiotic Resistance Genes Through Metagenomics - Lopez-Perez, Marcos; Mirete, Salvador (Recent Advances in DNA & Gene Sequences (Discontinued), 2014)
Antibiotic resistance (AR) represents a challenge for the treatment of infectious diseases. Traditionally, antibiotic resistance determinants have been retrieved from culturable bacteria which represent a minor fraction of the total microbial diversity found in natural environments such as soils. In this review, we summarize recent advances in the study of antibiotic resistance using two main culture-independent approaches: sequence-based metagenomics and functional metagenomics.
Keywords: Antimicrobial resistance